Potential Use of Euphorbia hirta for Dengue: A Systematic Review of Scientific Evidence - Sashini D. Perera; Uthpala A. Jayawardena; Chanika D. Jayasinghe (Journal of Tropical Medicine)
Euphorbia hirta commonly known as Tawa-Tawa is a plant used in folklore medicine in the Philippines for the treatment of dengue. Though, E. hirta has been extensively investigated for numerous bioactivities, limited studies have been conducted on the antidengue activity. Thus, the present study provides a comprehensive review of studies conducted on the antidengue activity of E. hirta. A systematic literature survey was carried out in scientific databases, PubMed®, Scopus, and Google Scholar, for research carried on the antidengue activity of E. hirta. The literature search identified a total of 867 articles: databases PubMed = 6, Scopus SciVerse® = 423, and Google Scholar = 437; one additional article was identified by searching reference lists. Eight full papers were entitled to the review; out of those, two studies focused on ethnobotanical surveys, three on animal experiments, one on human trial, and two on in vitro antiviral activities, and one was computational study. The available evidence conclusively demonstrates the potential of E. hirta against dengue as it holds significant antiviral and platelet increasing activities. However, the number of studies conducted to validate its antidengue activity was found to be inadequate. Hence, well-controlled clinical trials and contemporary pharmacological approaches including activity guided fractionation and elucidation of the mode of action are encouraged to establish the use of E. hirta for dengue.